2022
DOI: 10.1038/s41374-021-00681-8
|View full text |Cite
|
Sign up to set email alerts
|

The S100A10–AnxA2 complex is associated with the exocytosis of hepatitis B virus in intrauterine infection

Abstract: Mother-to-child transmission (MTCT) is the major cause of chronic infection of hepatitis B virus (HBV) in patients. However, whether and how HBV crosses the placenta to cause infection in utero remains unclear. In this study, we investigate the mechanism as to how the HBV virions pass through layers of the trophoblast. Our data demonstrate the exocytosis of virions from the trophoblast after exposure to HBV where the endocytosed HBV virions co-localized with an S100A10/AnxA2 complex and LC3, an autophagosome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Further, an association of HBV Pol- S100A10 with PML is increased by exposure of cells to EGTA but reduced by valinomycin ( Choi et al, 2003 ), suggesting that S100A10 modulates HBV Pol function, signaling the importance of PML nuclear bodies and intracellular Ca 2+ in HBV replication. It is also reported that A2t is associated with the exocytosis of HBV in intrauterine infection, which is the major cause of mother-to-child transmission (MTCT) ( Bai et al, 2022 ). Briefly, AnxA2 transferred from the cytoplasm to the surface of autophagosomes harboring HBV recruits S100A10 to form the heterotetramer A2t, which in turn recruits VAMP2, SNAP25 for membrane fusion so that the autophagosome fuses with MBV ( Bai et al, 2022 ).…”
Section: Impact Of Anxa2 On Virus Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Further, an association of HBV Pol- S100A10 with PML is increased by exposure of cells to EGTA but reduced by valinomycin ( Choi et al, 2003 ), suggesting that S100A10 modulates HBV Pol function, signaling the importance of PML nuclear bodies and intracellular Ca 2+ in HBV replication. It is also reported that A2t is associated with the exocytosis of HBV in intrauterine infection, which is the major cause of mother-to-child transmission (MTCT) ( Bai et al, 2022 ). Briefly, AnxA2 transferred from the cytoplasm to the surface of autophagosomes harboring HBV recruits S100A10 to form the heterotetramer A2t, which in turn recruits VAMP2, SNAP25 for membrane fusion so that the autophagosome fuses with MBV ( Bai et al, 2022 ).…”
Section: Impact Of Anxa2 On Virus Life Cyclementioning
confidence: 99%
“…It is also reported that A2t is associated with the exocytosis of HBV in intrauterine infection, which is the major cause of mother-to-child transmission (MTCT) ( Bai et al, 2022 ). Briefly, AnxA2 transferred from the cytoplasm to the surface of autophagosomes harboring HBV recruits S100A10 to form the heterotetramer A2t, which in turn recruits VAMP2, SNAP25 for membrane fusion so that the autophagosome fuses with MBV ( Bai et al, 2022 ). Then, HBV translocation across the trophoblast via A2t and MVB-mediated exocytosis occurs ( Bai et al, 2022 ).…”
Section: Impact Of Anxa2 On Virus Life Cyclementioning
confidence: 99%
“…Serum protein expression profiles of HBV were analysed by proteomics, and the expression of proteins related to intrauterine HBV transmission was further confirmed through immunohistochemistry and PCR techniques in both serum samples and placental tissues. After screening and identifying 35 differential proteins, we found that high expression levels of S100-family proteins and exocytosis mediated by the AnxA2-S100A10 complex were associated with intrauterine HBV transmission through the placenta 53,54 .…”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“… 15 Our recent study demonstrated the transcytosis of HBV across trophoblasts using trophoblastic cell line Swan71 and primary trophoblasts. 51 BeWo cells could actively transcytose HBIG and the reduced virus transcytosis rate was thought to be due to the formation of HBV-IgG complexes which were internalized via the Fc γ receptor. 15 , 52 Additionally, HBV transcytosis efficiency was reduced with the fusion of cytotrophoblasts into syncytiotrophoblasts and with the addition of HBIG.…”
Section: Molecular Mechanism Of Trophoblast Infection With Hbvmentioning
confidence: 99%